Experimental study of surface roughness effects on hydrodynamic characteristics of a submerged floating tunnel - Zou, P.X.; Ruiter, N.; Uijttewaal, W.S.J.; Chen, X.X.; Peters, D.J.; Bricker, J.D. (Applied ocean research, 2023)
Marine biofouling is a major concern in the operational performance of submerged floating tunnels (SFTs). The objective of this research is to investigate the effects of marine fouling (represented by surface roughness) on the hydrodynamic behavior of SFTs, including the hydrodynamic forces on the SFT subject to current-only, wave-only, and combined current-wave flow conditions. The effects of increased surface roughness induced by marine fouling on the dynamic response of an SFT are characterized by hydrodynamic force coefficients, including drag and inertia coefficients. At the Water Lab of Delft University of Technology (TU Delft), experiments have been performed in a wave-current flume to compare the SFTs’ behaviors as affected by different roughness characteristics. In addition, a parametric cross-section for an SFT is presented, and the hydrodynamic performance associated with surface roughness effects on the parametric shape and circular SFT cross-section shape are compared. The results show that the parametric shape can effectively reduce the drag coefficient (Cd) under current-only conditions and lower the inertia coefficient (Cm) when waves are present. As roughness height and coverage ratio increase, Cd generally increases while Cm decreases. However, small differences in Cd and Cm can be observed with regard to roughness parameters for wave-only conditions. The Morison coefficients adapted for a marine-fouled SFT measured in the experiments are compared to predictions from engineering standards and are recommended for engineering practice.